Pengabdian KKN Kepada Masyarakat Melalui Pelayanan Kesehatan Masyarakat di Desa Panta Dewa - Muhammad Rafly Akbar; Medy Purwanto; Theresia Fadirubun; Tia Ivanka; Elsi Deska Putri; Hatifah Hatifah; Rinni Gusanti; Hasri Pajar Lestari; Putri Adelia Maharani; Tri Satria Ramadhan; Winda Safitri; Deby Yulitasari; Nuril Fazriah; Winda Lusiati; Putri Lisa Ardiyani; Chantika Dela Putri Rusadi; Aprilia Novianti; Nyimas Rahma Komariah (JURNAL PENGABDIAN KADER BANGSA, 2026)
Health Services as the spearhead of all regulations, systems, and policies regarding Health. KKN students become role models for carrying out community service in accordance with applicable regulations. The desire is that the arrival of students will provide a breath of fresh air for cadres to share experiences, knowledge, and motivation. The purpose of this study is to describe the activities of the KKN work program in Panta Dewa village. The research method this time is included in qualitative research. Data collection techniques with observation, interviews, and documentation. This means that researchers collect data and then analyze it according to research needs. KKN was carried out from February 11-24, 2025 or 14 days of service in Panta Dewa Village. The results of this study are that KKN students carried out 8 work programs including Village Community Deliberations, Counseling and Education, Free Examination, Posyandu for Pregnant Women and Toddlers, and Joint Gymnastics. The conclusion of this study states that the community is impressed with the activities carried out and will always be committed to continuing these activities in the future.